Penerapan Model Pembelajaran Project Based Learning (PJBL) dalam Menyusun Karya Ilmiah Berbasis Kontekstual pada Siswa Kelas XI SMA Negeri 3 Palembang - Karmila, Emi; Lestari, Hikmah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is 1) to improve learning outcomes in compiling contextually based scientific work through the Project Based Learning (PJBL) learning model for class XI students at SMA Negeri 3 Palembang. 2) improve procedures for implementing the Project Based Learning learning model in compiling contextual-based scientific work for class XI students at SMA Negeri 3 Palembang. This research is Classroom Action Research (PTK) using the Kemmis and Mc Taggart model. This research uses a qualitative and quantitative descriptive research design with a collaborative pattern, researchers and teachers jointly carry out CAR to solve the problem to be researched. Data were collected through observations and tests which were analyzed descriptively qualitatively and quantitatively. Students prepared contextually based scientific work in class XI SMA Negeri 3 Palembang. The increase in the pre-cycle stage was 26.08% in the very good category, 17.39% in the good category, 32.60% in the moderate/fair category and 23.91% in the poor category. After implementing the first cycle actions, 34.78% were in the very good category, 30.43% were in the good category, 21.73% were in the moderate/fair category and 13.04% were in the poor category. Cycle II, 52.17% in the very good category, 39.13% in the good category, 10.86% in the moderate/fair category. Thus, the results of the performance test show that the learning outcomes of applying the Project Based Learning (PjBL) learning model in compiling contextual-based scientific work in class XI students at SMA Negeri 3 Palembang have increased.